Problems of Students' Critical Thinking on the Material of Straight Line Equations of Students of SMP Muhammadiyah Larangan - Saudah Saudah; Fitrianto Eko Subekti (UM Purwokerto Press, 2025)
This study aims to describe the difficulties of students' critical thinking skills. The research method used was qualitative descriptive with data collection techniques through written tests and interviews. Written tests are used to find out students' difficulties in solving problems while interviews are used to dig deep into information to find out information related to problem solving. The subject of this study is grade VIII students of SMP Muhammadiyah Larangan. The material used is a straight line equation. Data analysis was carried out by triangulation, which is comparing data from sources (written tests and interviews). The results of the study showed that: 1) high category students did not experience difficulties in solving problems, namely interpreting, analyzing, solving problems, and conducting evaluations, but students experienced difficulties in making inferences or drawing conclusions; 2) Medium category students do not experience difficulties in interpreting, analyzing, and solving problems, but students have difficulties in conducting evaluation and inference. 3) Low-category students have difficulty in solving problems because students have difficulties in interpreting, analyzing, solving problems, evaluating and drawing conclusions in solving problems. Based on the results of the study, it shows that students are not used to solving contextual problems so that students need to be accustomed to working on contextual problems so that they do not experience difficulties in critical thinking.